The Perspective of Islamic Economic Philosophy, Management, and Investment Decisions in Critique of Conventional Systems - Arif Surahman; Muhardi Muhardi; Jamaludin Jamaludin; Kartono Kartono; Achmad Agus Yasin Fadli (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2026)
This article examines the critique of conventional economic and strategic management paradigms and extends the discussion by integrating Islamic investment decision making. The study is conducted through library research by drawing on core books in Islamic finance and international journal articles on governance, investor behavior, Shariah markets, and portfolio decision making. The findings indicate that conventional systems are largely grounded in profit maximization, instrumental rationality, and value-neutral assumptions, making them prone to inequality, risk shifting, speculation, and the neglect of moral responsibility in decision processes. In contrast, the Islamic perspective regards economic, strategic, and investment activities as a trust that must be managed within the framework of justice, public welfare, blessing, and maqasid al-shariah. Ontologically, human beings are viewed as caliphs; epistemologically, decisions are formed through revelation, reason, and empirical experience; and axiologically, investment and organizational management must conform to trustworthiness, transparency, risk sharing, prudence, and moral-spiritual accountability. This integration offers a more holistic paradigm for organizational management and investment decision making, since it evaluates not only financial outcomes but also process quality, contractual justice, social impact, and ethical accountability.